Experimental analysis of embankment on soft soil improved with bottom ash columns. (November 2022) - Ullah, Arshad; Kassim, Azman; Ahmed, Sarfraz; Ullah, Rafi; Junaid, Muhammad; Danish Zia, Muhammad
Abstract: Bottom ash is a byproduct formed during the combustion of coal and can be used as an alternative to aggregate and sand as a green material in columns to achieve sustainability in ground improvement. In this study, the bearing capacity performance of highway embankment models constructed on bottom ash columns reinforced soil was investigated. Model tests were carried out with various area replacement ratios (Ar) of 10.91 %, 16.37 % and 21.83 % and column length to diameter ratios (L/D) of 6 and 8. Load cell and three miniature pressure transducers were used for the measurement of vertical stress on the embankment surface, top and base of the column and adjacent soil surrounding the columns. A Pore pressure transducer was employed to record the excess-pore water pressure during the loading test. The stress concentration ratio and column failure modes were investigated for the stress transfer mechanism. The tests results revealed that bottom ash columns, whether floating or end bearing, was most effective in enhancing the ultimate bearing capacity (qult ) of improved soil at almost 1.24, 1.39 and 1.63 times and 1.27, 1.42 and 1.83 times that of unreinforced soil for Ar of 10.91 %, 16.37 % and 21.83 % with L/D of 6 and 8, respectively. The stress concentration ratio (SCR) increased with higher Ar and L/D values. The highest improvement ratio was obtained for the model improved with bottom ash columns at Ar = 21.83 % and L/D = 8. The end-bearing bottom ash columns fail by bulging and floating bottom ash columns fail by bulging along with punching at the base. Furthermore, a mathematical expression with R 2  = 0.9913 was developed for calculating the approximate qult . The approximate qult are in good agreement with actual qult . The findings of this study resulted in the utilization of bottom ash as a sustainable granular material in the column for the ground improvement underneath embankments.